ANALISIS KONFLIK SOSIAL DALAM NOVEL SI ANAK BADAI KARYA TERE LIYE : KAJIAN SOSIOLOGI SASTRA - Maguna Eliastuti; Ana Triyana; Fachri Aulia; Fathia Fidzri Aulia; Nur Amaliyah (JISOS: JURNAL ILMU SOSIAL, 2023)
The study entitled "Social Conflict in the Novel Si Anak Storm Study of Sociology of Literature", the researcher feels that the social conflict raised in the novel is a social conflict that must be discussed and found solutions and lessons learned. In the novel The Child of the Storm by Tere Liye, the author discusses the routine activities of the children of Manowa village, namely waiting for ships from the sea to head upstream, or ships from the upstream that sail towards the sea. Activities carried out every Sunday afternoon or every red date of school holidays. Our village is located right at the mouth of a large river which is the crossing for ships heading to the next village or town, the ship docks at the pier if there are passengers from the village but more just pass by. When the ship passes, that's when the children of Manowa village do their action. They will swim beside the ship, waving their hands to the passengers, waiting for them to throw coins down, then they scramble to take the money and problems arise when Manowa village is made a big port. With this research, it is hoped that it can provide benefits and as input or lessons that courage and cooperation will produce the desired results. This study analyzes data in the form of Tere Liye's novel The Child of Storms, which displays data as it is without any manipulation process. Qualitative descriptive research is used to analyze events, phenomena or situations socially. Based on the results of the research, the forms of social conflict experienced by the characters are tension, rejection, courage and the biggest conflict or the source is the port construction case.